2015
DOI: 10.1155/2015/439370
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinoma: A ceRNA Analysis Pointed to a Crosstalk betweenSOX2,TP53, and microRNA Biogenesis

Abstract: It has been suggested that cancer stem cells (CSC) may play a central role in oncogenesis, especially in undifferentiated tumours. Anaplastic thyroid carcinoma (ATC) has characteristics suggestive of a tumour enriched in CSC. Previous studies suggested that the stem cell factor SOX2 has a preeminent hierarchical role in determining the characteristics of stem cells in SW1736 ATC cell line. In detail, silencing SOX2 in SW1736 is able to suppress the expression of the stem markers analysed, strongly sensitizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, they show the ability to combine the same miRNA varies with each other, thus constructing multiplex RNA regulatory networks centered on miRNA. This network regulates RNA expression level, allow them to influence each other, and eventually affect the function of cells, which is called competitive endogenous RNA (ceRNA) mechanism 9,10 . Long noncoding RNA (lncRNA) is a noncoding protein‐nucleic acid sequence with a length of more than 200 bp, which is critical for the incidence and progression of cancers including BC 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they show the ability to combine the same miRNA varies with each other, thus constructing multiplex RNA regulatory networks centered on miRNA. This network regulates RNA expression level, allow them to influence each other, and eventually affect the function of cells, which is called competitive endogenous RNA (ceRNA) mechanism 9,10 . Long noncoding RNA (lncRNA) is a noncoding protein‐nucleic acid sequence with a length of more than 200 bp, which is critical for the incidence and progression of cancers including BC 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…ceRNAs are RNAs that share miRNA recognition elements (MREs) thereby competing for miRNA binding and regulating each other. Numerous recent studies of mammalian cells and tissues have demonstrated the competition between the protein-coding targets of miRNAs, which supportis a regulatory role for mRNAs independent of their protein coding function (13,14). Large-scale analyses of human gliomas have led to the conclusion that thousands of transcripts may act as target decoys, and the combined effects of multiple ceRNAs can have a major impact on gene expression and cellular phenotypes (15,16).…”
Section: Introductionmentioning
confidence: 94%
“…PGG family 1149 is of interest because it contains the proto-oncogene RELA which has been implicated in pseudogene regulatory activity 34,35 . Another family of interest is 1235 that contains SOX2, which has been identified as a member of ceRNA networks 36,37 .…”
Section: Resultsmentioning
confidence: 99%